The role of political connections as a moderating determinant of tax avoidance - Umi Laila Aristiyaningrum (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Taxes are a primary source of state revenue to finance development and public welfare. However, the government's interest in optimizing tax revenue often conflicts with companies, who view taxes as a significant burden, thus encouraging tax avoidance practices. Indonesia's low tax ratio and fluctuations in mining sector tax revenues indicate the potential for such practices. Thin capitalization and transfer pricing schemes are suspected to be key strategies, with political connections amplifying them. This study examines the influence of these two strategies on tax avoidance, with political connections acting as a moderating variable. Methods: The sampling technique used in this study was purposive sampling, resulting in a sample of 44 mining companies listed on the Indonesia Stock Exchange from 2013 to 2022. The method used in testing the hypothesis was the Generalized Method of Moment (GMM). Findings: The results of this study indicate that thin capitalization and transfer pricing have a significant effect on tax avoidance. In addition, this study reveals that political connections can moderate the effect of thin capitalization and transfer pricing on tax avoidance. Conclusion Research shows that thin capitalization increases tax avoidance, transfer pricing decreases it, and political connections moderate both, implying more effective and comprehensive tax regulations. Novelty/Originality of this article: This research is one of the studies that examines thin capitalization and transfer pricing in tax avoidance with political connections as a moderating variable. Political connections were chosen as a moderating variable because they are thought to have a non-technical effect on tax avoidance practices carried out by companies.